Daya Serap Materi Pelajaran dan Reliabilitas Tes Matematika Bentuk Soal Uraian - Fahmi, NFN (Pusat Asesmen dan Pembelajaran, 2020)
This study aims to determine the proportion correct of mathematics subject matter and compare the reliability of essay tests that are scored with 3 different rubric models. The method used in this research is an experiment using design treatments by subjects, an experiment using one group (one group experiment) which is also an experimental group and a control group in different experimental periods. Schools that were sampled were 6 public and private junior high schools and students were sampled as many as 452 students. The research sample was determined by two-stage stratified random sampling. The objects in this study consisted of 22 essay questions in Mathematics for junior high school compiled from the same test specifications. Scoring uses 3 scoring rubrics models, namely scoring rubric Model 1 (0,1), Model 2 (0,1,2), and Model 3 (keywords). The results obtained from this study indicate the reliability of the mathematical essay test on the scoring rubric of model 1 is 0.6859, model 2 is 0.7025, and model 3 is 0.6986. Test reliability of the three scoring rubrics is high or reliable. Students' competence in completing mathematical essay questions is still low, which is under 50%. Only mathematical essay questions calculate volume at the cognitive level of knowledge and understanding above 70%. Student competencies in solving questions that measure reasoning is an average of 12.20%. In other words, the proportion correct of subject matter in two-dimentional figure and space less than 50%, this shows that students still do not understand the concept of the subject matter, especially the material of the central angular relationship, arc length, sector area, which can only be answered correctly by 17.58% of students.